Belief updating in individual and social learning: A field experiment on the internet - Shunichiro Sasaki; Toshiji Kawagoe (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We conducted a field experiment on the Internet and investigated the participants' belief updating in an individual learning environment where they observe a sequence of private signals and in a social learning environment where they observe a sequence of other people's actions. We observed that participants do not update their posterior beliefs as efficiently as Bayesian, and that participants rely more on private signals than on other people's actions even when the informativeness of both is identical. Furthermore, we confirmed that participant's trust in other people's actions and their conformity to other people's actions are affected by their demographic characteristics.
Keywords: C93; D83; 330; belief updating; individual learning; social learning; field experiment; conformity; Bildungsverhalten; Soziale Kompetenz; Test; Internet; Japan